Study of qualitative and quantitative indicators of the spermatogenesis for determination of the effectiveness of cryopreservation (International Journal of Biology and Chemistry, 2018)
Semen or spermatozoa cryopreservation (commonly called sperm banking) is a procedure to preserve sperm cells. Semen can be used successfully indefinitely after cryopreservation and might be stored successfully over 20 years. It can be used for sperm donation where the recipient wants the treatment in a different time or place, or as a means of preserving fertility for men undergoing vasectomy or treatments that may compromise their fertility, such as chemotherapy, radiation therapy or surgery. However, before the cryopreservation, it is necessary to check the parameters of the ejaculate and treat the sperm in a special container (a small in diameter plastic box with information about the patient) to increase the concentration ofspermatozoa. Put the container for storage into Dewar tube. In some cases, cryopreservation might worsen the quality of the ejaculate. After freezing, the mobility and morphology of the sperm can deteriorate. Thus, it is desirable to carry out freezing in test conditions to determine the need for the frozen material. Especially when spouses plan to use additional fertilization programs, this approach should be taken into account, since cryopreservation might cause a spontaneous change in the program of intracytoplasmic vaccination of the spouse. One of the methodological problems of cryopreservation is poor quality of the ejaculate, i.e. when freezing spermatozoa, their activity and function deteriorate from the norm. This reduces the possibility of using them in the future for artificial insemination. Results of the experiment show that cryopreservation is possible only in specialized centers with the highest professional standards.